The Manajemen Pembelajaran Berbasis Kelas Cerdas Untuk Meningkatkan Hasil Belajar Siswa SMAIT Al-Multazam 2 Kabupaten Linggajati Kuningan - Edi Gunarto; Hurriyah; Didin Nurul Rosidin (Sekolah Tinggi Ilmu Tarbiyah Buntet Pesantren Cirebon, 2023)
This study aims to: 1) Describe Smart Classroom-based Learning Planning at SMAIT Al-Multazam 2 Linggajati, 2) Describe Smart Classroom-based learning organization at SMAIT Al-Multazam 2 Linggajati, 3) Describe Smart Classroom-based learning at SMAIT Al-Multazam 2 Linggajati, 4) explanation of limitations on Smart Classroom-based learning at SMAIT Al-Multazam 2 Linggajati, 4) Verifying evaluation in Smart Classroom-based learning at SMAIT Al-Multazam 2 Linggajati. The method used in this study is qualitative research which seeks to solve problems encountered during research with data collection techniques through observation, interviews, and study documents. While the data analysis technique is done by data reduction, data presentation, and drawing conclusions. The research results obtained are: 1) The smart classroom-based learning process involves all levels of management in an institution so that the program runs well. Besides that, the teacher specifically also makes smart classroom-based learning plans contained in the lesson plans. 2) Organizing in a smart classroom includes organizing program implementation which is carried out by dividing team assignments, as well as organizing learning activities in class, which are also carried out for specific purposes. 3) In implementing smart classroom-based learning, the teacher optimizes the use of the smart classroom component to support the learning climate. 4) To carry out program control, it is carried out through evaluation meetings. Meanwhile, the control of learning activities in class is carried out through a systems approach and a behavioral approach. 5) Evaluation for smart classroom-based learning is carried out periodically both to assess the running of the program and to assess student learning outcomes in both cognitive, affective and psychomotor aspects.